Most Assuredly Perpetual Motion: Police and Policing in Quebec City, 1838-58 - McCulloch, Michael (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1990)
This paper examines the evolution of the structure and function of Quebec City's police force. Originally conceived as an instrument of British authority, it was remodelled along Utilitarian lines. Provincial and municipal authorities disputed its control; both levels of government, however, shared the same professional and disciplined model of a force detathced from the people. This ideal did not become a reality. The structure of Quebec society and the limitations of municipal power ensured that the police force was more concerned with routine 'service' functions than with social control. The conditions in the city played a larger role in shaping the force than the theories of police reformers.